REVITALISASI NILAI-NILAI KARAKTER NGGUSU WARU SEBAGAI PEMBANGUNAN UTAMA PENDIDIKAN KARAKTER ANAK DI BIMA - Abd Salam (Prodi PGMI STIT Sunan Giri Bima, 2022)
The fostering of Nggusu Waru values ​​is able to change regeneration for the better. the values ​​contained in nggusu waru are not only character but Islamic values ​​which are believed to be able to protect them from despicable things. With the crisis of character, adab at this time, the main pillars of the sultan and the people of Bima are the Book of Allah (Al-Qur'an) and Al-Hadith besides the guidance and development is